2002
DOI: 10.1302/0301-620x.84b2.11923
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised trial of internal fixation <I>versus</I> arthroplasty for displaced fractures of the neck of the femur: Functional outcome for 450 patients at two years

Abstract: It remains a matter of debate whether displaced fractures of the neck of the femur should be treated by internal fixation or arthroplasty. We have compared the two methods with regard to complications, mortality and functional outcome. We studied 409 patients, aged 70 years and over, with subcapital fractures graded as Garden 3 or 4, in a two-year prospective multicentre study from 12 Swedish hospitals. They were randomised to internal fixation or arthroplasty. Patients who were mentally confused, bedridden or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
193
6
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(214 citation statements)
references
References 24 publications
11
193
6
4
Order By: Relevance
“…The overall short life expectancy and the superior shortterm function in the hemiarthroplasty group reinforce bipolar hemiarthroplasty as the treatment of choice in elderly patients with a displaced intracapsular hip fracture [10,13,29,33]. The excess mortality compared with the background population is well demonstrated for the first year after fracture [20].…”
Section: Discussionmentioning
confidence: 91%
“…The overall short life expectancy and the superior shortterm function in the hemiarthroplasty group reinforce bipolar hemiarthroplasty as the treatment of choice in elderly patients with a displaced intracapsular hip fracture [10,13,29,33]. The excess mortality compared with the background population is well demonstrated for the first year after fracture [20].…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies have provided evidence for better outcomes after arthroplasty (HA or THA) as compared with internal fixation [4,7,10,11,17,[20][21][22]. Blomfeldt et al performed a randomized, controlled trial of 102 elderly patients with displaced femoral neck fractures [7].…”
Section: Discussionmentioning
confidence: 99%
“…Revision rates were 4% in the THA group and 47% in the internal fixation group. Rogmark et al performed a similar study comparing arthroplasty with internal fixation [20] and reported higher rates of failure and poor functional outcomes, as measured by pain and impaired walking ability, in patients undergoing internal fixation as compared with arthroplasty. Bhandari et al reported a meta-analysis of randomized trials comparing arthroplasty and internal fixation between 1969 and 2002 [4].…”
Section: Discussionmentioning
confidence: 99%
“…In contrary, the influence of the surgical management in this regard seems to be of minor importance. Numerous randomized controlled trails (RCTs) and meta-analyses demonstrated no difference in one year mortality between internal fixation (IF) and hemiarthroplasty (HA) [8][9][10][11][12] . But many of these studies restrict their inclusion criteria to only a subset of patients which might result in considerable bias.…”
Section: Influence Of Internal Fixation and Cemented Hemiarthroplastymentioning
confidence: 99%
“…But many of these studies restrict their inclusion criteria to only a subset of patients which might result in considerable bias. For instance, several RCTs exclude patients with cognitive impairment [10,11] which on the other side comprise up to 30% of elderly patients with hip fracture [8,13] . Cognitive impairment was identified as a risk factor for mortality in these patients [4,13] .…”
Section: Influence Of Internal Fixation and Cemented Hemiarthroplastymentioning
confidence: 99%